PENGARUH PENERAPAN MOVING CLASS TERHADAP EFEKTIVITAS PEMBELAJARAN PADA MATA PELAJARAN PENDIDIKAN KEWARGANEGARAAN - citra abdi negari; Berchah Pitoewas; Yunisca Nurmalisa (Jurnal Kultur Demokrasi, 2012)
The purpose of this study to explain include of moving class aplications towards learning effectiveness on ten class citizenship education at SMK N 5 Bandar Lampung lesson year 2012/2013. This research method using descriptions method is quantitative. Sample this research 32 respondent. Data analysis using Chi Square.Based on the result show presence significant include between moving class aplications towards learning effectiveness on ten class citizenship education at SMK N 5 Bandar Lampung lesson year 2012/2013. Be evidenced with calculation result using Chi Square formula so that for moving class applications towards learning effectiveness on citizenship education obtainable contingency coefficient C= 0,62 and maximum contingency coefficient  = 0,812. According to these calculations then contingency coefficient C=0,62 in the category of strong. This suggests that include of moving class aplications towards learning effectiveness on ten class citizenship education at SMK N 5 Bandar Lampung lesson year 2012/2013 has a strong influence level of closeness.Key words : Moving class, learning effectiveness